2016
DOI: 10.4236/aad.2016.52005
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of <i>Phyllanthus acidus</i> L. on Learning and Memory Impairment in Scopolamine-Induced Animal Model of Dementia and Oxidative Stress: Natural Wonder for Regulating the Development and Progression of Alzheimer’s Disease

Abstract: Nature is the best source of complementary and alternative medicine. The plant Phyllanthus acidus (PA) L. has been used traditionally in pain, inflammatory and oxidative stress related disorders. In this consequence, methanolic extract of PA (MEPA) was selected to explore the ability of this plant to enhance cognitive function, brain antioxidant enzymes and anti-acetylcholinesterase activity which can be used for the treatment of oxidative stress related disorders like Alzheimer's disease (AD). The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 57 publications
4
34
0
Order By: Relevance
“…The results of this study exposed that AChE activity was significantly decreased in the EEPR treated rats. In the study of neuro-protective effect of Phyllanthus acidus fruits on learning and memory impairment in scopolamine-induced animal model of dementia and oxidative stress, Uddin et al, disclosed increases brain acetylcholine levels and enhances cognitive function in rats [87].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study exposed that AChE activity was significantly decreased in the EEPR treated rats. In the study of neuro-protective effect of Phyllanthus acidus fruits on learning and memory impairment in scopolamine-induced animal model of dementia and oxidative stress, Uddin et al, disclosed increases brain acetylcholine levels and enhances cognitive function in rats [87].…”
Section: Discussionmentioning
confidence: 99%
“…Universally common neurological disorders are epilepsy, Alzheimer’s disease (AD), and other dementias, headache, migraine, multiple sclerosis (MS), neuroinfections, Parkinson’s disease (PD), stroke, brain tumors, brain trauma, malnutrition-related neurological disorders, and so on, [9-12]. Neurological disorders can be life threatening, similar to brain tumors and strokes or less harmful, similar to tension headaches and sleep disorders [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, AChE activity was decreased in both SS and DS portions, with significant effects in rats treated with unripe fruit extract as compared to the control group. Uddin et al [79] showed that the administration of Phyllanthus acidus fruit increases the brain acetylcholine levels and enhances the cognitive function in rats, while attenuating memory deficits in animal model of amnesia. Our results projected that administration of EEPEr fruit, especially higher dose (i.e., 200 mg/kg b.w.)…”
Section: Discussionmentioning
confidence: 99%